Case report: Intrafraction dose-guided tracking for gastrointestinal organ-at-risk isotoxicity delivery on an MR-guided radiotherapy system - Yarlagadda, Sreenija; Weiss, Yonatan; Chuong, Michael David; Bassiri, Nema; Gutierrez, Alonso N.; Kotecha, Rupesh; Mehta, Minesh P.; Mittauer, Kathryn Elizabeth (Frontiers in Oncology, 2024)
In the current era of high-precision radiation therapy, real-time magnetic resonance (MR)-guided tracking of the tumor and organs at risk (OARs) is a novel approach that enables accurate and safe delivery of high-dose radiation. Organ tracking provides a general sense of the need for daily online adaptation but lacks precise information regarding exact dosimetry. To overcome this limitation, we developed the methodology for monitoring intrafraction motion with real-time MR-guided isodose line-based tracking of an OAR in combination with anatomic tumor-based tracking and reported the first case treated with this approach. An isolated para-aortic (PA) nodal recurrence from carcinosarcoma of the endometrium was treated with an ablative dose of 50 Gy in five fractions using MR-guided radiotherapy (MRgRT). This report demonstrates the feasibility, workflow, dosimetric constraints, and treatment paradigm for real-time isodose line-based OAR tracking and gating to enable an isotoxicity delivery approach. This innovative treatment strategy effectively tracked the intrafraction motion of both the target and OAR independently and enhanced the accuracy of structure localization in time and space with a more precise dosimetric evaluation.